Sufficient conditions for the existence of points of symmetric quasicontinuity and of symmetric cliquishness of functions of two variables - Nesterenko, V.V. (Carpathian Mathematical Publications, 2011)
It is established sufficient conditions under which for the function f:X× Y→ Z there is a residual in X set A, such that the function f is symmetrically quasi-continuous (cliquish) one with respect to x at each point of the set A× Y.